Genomic analysis of Brevibacillus thermoruber 423 reveals its biotechnological and industrial potential - TOKSOY ÖNER, EBRU; ARĞA, KAZIM YALÇIN (SPRINGER, 2015)
Brevibacillus thermoruber 423 is a Gram-positive, motile, red-pigmented, spore-forming, aerobic, and thermophilic bacterium that is known to produce high levels of exopolysaccharide (EPS) with many potential uses in food, feed, cosmetics, and pharmaceutical and chemical industries. This bacterium not only is among the limited number of reported thermophilic EPS producers but also exceeds other thermophilic producers in light of the high level of polymer synthesis. By a systems-based approach, whole-genome analysis of this bacterium was performed to gain more insight about the biological mechanisms and whole-genome organization of thermophilic EPS producers and hence to develop rational strategies for the genetic and metabolic optimization of EPS production. Also with this study, the first genome analysis was performed on a thermophilic Brevibacillus species. Essential genes associated with EPS biosynthesis were detected by genome annotation, and together with experimental evidences, a hypothetical mechanism for EPS biosynthesis was generated. B. thermoruber 423 was found to have many potential applications in biotechnology and industry because of its capacity to utilize xylose and to produce EPS, isoprenoids, ethanol/butanol, lipases, proteases, cellulase, and glucoamylase enzymes as well as its resistance to arsenic.
Keywords: Brevibacillus thermoruber; Thermophiles; Genome; Next-generation sequencing; Exopolysaccharide; SP-NOV; GLYCINE BETAINE; SEQUENCE; PROTEIN; EXPRESSION; SUBTILIS; REV